Integrated static and dynamic geophysical and geomechanical data for characterization of transport properties. (May 2022) - Mallet, C.; Isch, A.; Laurent, G.; Jodry, C.; Azaroual, M.
Abstract: The observatory of transfers in the vadose zone (OZNS-France) offers a unique support for characterizing the Beauce limestone aquifer at various spatial and temporal scales. This observatory consists of a large well associated with external boreholes dedicated to imaging, monitoring, and understanding mass and heat transfers through the vadose zone. An initial geological characterization of core samples gave valuable information on the facies encountered within the vadose zone. It is composed of highly incoherent limestones down to 7 m-depth and a massive and altered limestone rock layer from 7 to 20 m-depth. The latter presents fracturation and karstification increasing with depth. This study focuses on the hard limestone rock units and aims to quantify the level of heterogeneity through static and dynamic laboratory tests performed on core samples. Along 20 m of three boreholes, representative samples are tested through uniaxial or triaxial conditions. Elastic wave velocities are also measured. The obtained Young's modulus, compression strength, and P- and S-wave velocities highlight strong variations with depth. For example, at 14 m-depth, uniaxial maximal strength ranges from 13 to 123 MPa. In addition, at 16 m-depth, P-wave velocities are distributed from 3, 650 to 5, 700 m.s −1 . These large scatterings confirm the strong heterogeneity of the geological formations. It is interpreted in terms of a high porosity, degree of fracturation and/or initiate active karstification. The double porosity is discussed from the difference between the static and dynamic Young's modulus. Their variations are interpreted in terms of connected porosity and important crack density. This last parameter is estimated from the P- and S- wave velocities, and ranges from 0 to 0.43, with an extremum value of 1.21 around 19 m-depth. These values and variations are in good correlation with log imaging and independent permeability laboratory measurements made on the hard limestone rock units. Highlights: Coupled methods allow to characterize transport property of heterogeneous limestones. Comparison of static and dynamic data shows a strong variation in double porosity. High heterogeneities are in good correlation with permeability measurements.